Performance Analysis of Pedestrian Roads Around the Andi Pangeran Pettarani Road Corridor, Makassar City - Lili Lili; Muhammad Yamin Jinca; Idawarni J. Asmal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Street Andi Pangeran Pettarani is one of the protocol roads in Makassar City and is located in a strategic area. Residential buildings along the Andi Pangeran Pettarani axis road have now turned into commercial buildings such as culinary or restaurant buildings, shops, hotels, offices, non-formal formal educational institutions, and even health services such as clinics and hospitals. The owner of the building builds in the border area of the building for these commercial activities. This then causes the unavailability of parking space for vehicles. Visitors who have vehicles will use sidewalks, road shoulders and even part of the road as a parking lot so that pedestrian paths in the form of sidewalks become unsafe and comfortable. The study was conducted on the sidewalk along the corridor of Andi Pangeran Pettarani, Panakkukang District, Makassar City. The 4 kilometer long axis road is divided into 6 segments for easy observation. This study aims to evaluate the utilization and availability of sidewalk support facilities and the level of pedestrian satisfaction with the sidewalks along the Andi Pangeran Pettarani road corridor. The method used is descriptive analysis method to describe the results of observations of the use and availability of sidewalk supporting facilities; IPA (Importance Performance Analysis) analysis to determine the level of performance and importance of each supporting facility in order to prepare recommendations for the direction of the pedestrian path improvement plan.